Comparative study of selected indoor concentration from selective laser sintering process using virgin and recycled polyamide nylon (pa12) - Damanhuri, A A M; Subki, A S A; Hariri, A; Tee, B T; Fauadi, M H F M; Hussin, M S F; Mustafa, M S S (2019)
Additive manufacturing (AM) stands out as one of the promising technologies that have huge potential towards manufacturing industry. The study on additive manufacturing impact on the environment and occupational exposure are attracting growing attention recently. However, most of the researcher focus on desktop and fused deposition modelling type and less attention given to the industrial type of AM. Usually, during the selective laser sintering process, recycle powder will be used again to reduce cost and waste. This article compares the PM 2.5, carbon dioxide (CO2) and total volatile organic compound (TVOC) concentration between virgin and recycles powder using polyamide-nylon (PA12) towards indoor concentration. Four phases of sampling involve during air sampling accordingly to the Industry Code of Practice on Indoor Air Quality 2010 by DOSH Malaysia. It was found that PM 2.5 and CO2 concentration are mainly generated during the pre-printing process. The recycle powder tended to appear higher compared to virgin powder in terms of PM 2.5, and CO2. The peak value of PM 2.5 is 1452 μg/m3 and CO2 is 1218 ppm are obtained during the pre-printing process during 8 hours of sampling. TVOC concentration from recycling powder is slightly higher during the post- printing phase where confirm the influence of the powder cake and PA12 temperature from the printing process. In summary, this work proves that elective laser sintering (SLS) machine operators are exposed to a significant amount of exposure during the SLS printing process. Mitigation strategies and personal protective equipment are suggested to reduce occupational exposure.